Research progress of phosphatidylinositol 4-kinase and its inhibitors in inflammatory diseases - Li, Yan-ping; Mikrani, Reyaj; Hu, Yi-fan; Faran Ashraf Baig, Mirza Muhammad; Abbas, Muhammad; Akhtar, Fahad; Xu, Ming (European journal of pharmacology, 2021)
Phosphatidylinositol 4-kinase (PI4K) is a lipid kinase that can catalyze the transfer of phosphate group from ATP to the inositol ring of phosphatidylinositol (PtdIns) resulting in the phosphorylation of PtdIns at 4-OH sites, to generate phosphatidylinositol 4-phosphate (PI4P). Studies on biological functions reveal that PI4K is closely related to the occurrence and development of various inflammatory diseases such as obesity, cancer, viral infections, malaria, Alzheimer's disease, etc. PI4K-related inhibitors have been found to have the effects of inhibiting virus replication, anti-cancer, treating malaria and reducing rejection in organ transplants, among which MMV390048, an anti-malaria drug, has entered phase II clinical trial. This review discusses the classification, structure, distribution and related inhibitors of PI4K and their role in the progression of cancer, viral replication, and other inflammation induced diseases to explore their potential as therapeutic targets.